Recent advances in steam reforming of glycerol for syngas production - Siang, Tan Ji; Nurul Asmawati, Roslan; Herma Dina, Setiabudi; Sumaiya, Zainal Abidin; Trinh Duy, Nguyen; Cheng, Chin Kui; Aishah, Abdul Jalil; Thang Le, Minh; Sarangi, Prakash K.; Nanda, Sonil; Vo, Dai-Viet N. (Springer, 2020)
Syngas, a mixture of carbon monoxide and hydrogen, has recently emerged as an important intermediate feedstock in petrochemical industry and an efficient and eco-friendly energy carrier to substitute petroleum-based fuels. Although methane is conventionally employed as a main feedstock for syngas production via industrial methane steam reforming process, a rising interest about the implementation of glycerol for generating syngas is widely reported in literature due to its great abundance, low cost, and hydrogen-rich content. This chapter summarizes the recent progress in catalytic steam reforming of glycerol for syngas yield in terms of catalytic design using various supports and promoters and the manipulation of operating variables. The mechanistic pathways and their fundamentally derived kinetic models for expressing glycerol reaction rate and estimating associated kinetic parameters are also comprehensively reviewed throughout this chapter.